Evaluation of gel chromatography for plasma lipoprotein fractionation - Teizo Sata; David L. Estrich; Peter D.S. Wood; Laurance W. Kinsell (Journal of Lipid Research, 1970)
The fractionation of lipoproteins of normal and hyperlipidemic subjects on a column of 2% agarose was compared with ultracentrifugation and paper electrophoresis procedures. The following results were obtained. (a) Plasma lipoproteins were eluted successively from the column in the four overlapping peaks of chylomicrons, very low density lipoproteins, low density lipoproteins, and high density lipoproteins. (b) Very low density lipoproteins and high density lipoproteins (d > 1.063, containing nonlipoprotein proteins) showed continuous progressive changes in lipid composition as these fractions emerged, while low density lipoproteins showed a relatively constant lipid composition. (c) A discontinuous transition of lipid composition was observed when consecutive ultracentrifugal fractions were placed on the column. (d) The “trail” of pre-beta lipoprotein seen on paper electrophoresis was shown to consist of particles whose molecular sizes range between chylomicrons and pre-beta lipoproteins. A reverse relationship was observed between electrophoretic mobilities of “trail” components and their particle size. (e) Gel with an agarose content of 2% seemed to fractionate chylomicrons and very low density lipoproteins more effectively than other lipoprotein classes.